Treatment of Arthrogenic-Muscle-Inhibition in patients after knee-surgery with Motion-Activated-Neuromuscular stimulation – a case-series - Schoepp, Christian; Dickschas, Jörg; Schmeling, Arno; Perwanger, Florian; Izadpanah, Kaywan; Praetorius, Arthur (Sportverletzung · Sportschaden, 2024)
Arthrogenic muscle inhibition (AMI) presents a persistent challenge in postoperative knee rehabilitation and is often resistant to standard care. This case series examines the efficacy of Motion-Activated Neuromuscular Electrical Stimulation (mNMES) in addressing AMI refractory to rehabilitation after ACL (revision) surgery, patellar dislocation, trochleoplasty, or conservative treatment of the patellofemoral pain syndrome. Eight patients who had undergone extensive unsuccessful rehabilitation received six weeks of a novel mNMES treatment regimen. Outcome assessments included patient-reported outcome measures (PROMs) and AMI classification. Results revealed significant improvements in pain reduction, knee function, and AMI reduction. Despite study limitations, mNMES demonstrated promising outcomes and could be used as an adjunct to standard rehabilitation, offering potential for enhancing postoperative outcomes in patients refractory to conventional therapy. Further research is required to validate these findings and optimise treatment protocols.
Keywords: arthrogenic muscle inhibition; neuromuscular stimulation; patellofemoral pain; anterior knee pain; anterior cruciate ligament revision surgery; trochleaplasty; knee pacemaker